GM agricultural technologies for Africa: A state of affairs - Chambers, Judith A.; Zambrano, Patricia; Falck-Zepeda, José B.; Gruère, Guillaume P.; Sengupta, Debdatta; Hokanson, Karen (International Food Policy Research Institute, 2014)
The African Development Bank (AfDB), in commissioning this report to be prepared by the International Food Policy Research Institute (IFPRI), highlighted the need for a comprehensive, evidenced-based review of agricultural biotechnology in order to better understand its current status, issues, constraints, and opportunities for Africa. Agricultural biotechnology comprises several scientific techniques (genetic engineering, molecular marker-assisted breeding, the use of molecular diagnostics and vaccines, and tissue cul-ture) that are used to improve plants, animals, and microorganisms. However, in prepar-ing this desktop analysis, IFPRI has focused on genetic modification (GM) technologies in particular and on the agricultural context in which they are being applied, because GM technologies are at the center of the controversy about biotechnology’s role in Africa. In addition, because we have attempted to focus our review on peer-reviewed evidence and documented examples, the preponderance of data presented in the report is focused on genetically modified (also abbreviated GM) crops in use and under development, although we recognize the potential of the technology for livestock, fisheries, and forestry.